Waterborne polyurethane nanocomposite reinforced with amine intercalated α-zirconium phosphate - Study of thermal and mechanical properties. (9th January 2020) - Kale, Manoj B.; Divakaran, Nidhin; Mubarak, Suhail; Dhamodharan, Duraisami; Senthil, T.; Wu, Lixin
Abstract: The in situ polymerization scheme was chose to introduce the amine intercalated α-zirconium phosphate (fZrP) in the waterborne polyurethane (WPU). The α-ZrP (ZrP) was prepared by refluxing zirconyl chloride octahydrate and then amine intercalated using ethylenediamine. The nanocomposites were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy and thermogravimetric analysis. The fZrP was introduced in the WPU with the known filler content of 0.1, 0.5 and 1 wt%, respectively. The prepared WPU/fZrP nanocomposites films have shown better mechanical, thermal and water resistance properties compared to the neat WPU and unmodified ZrP nanocomposites. The tensile strength of WPU filled with 1 wt% fZrP was increased by 57.09% against the WPU filled with 1 wt% unmodified ZrP. The thermal properties of the WPU showed increasing performance with the increasing fZrP content. The incorporation of fZrP in the WPU increased the thermal conductivity from 0.1777 W/m . K for virgin WPU and 0.2969 W/m . K for WPU/fZrP (1 wt%). The water resistance performance of the WPU was also improved with the increasing filler content. The results portray that the α-ZrP nanoplates can be an additive material to improve the thermo-mechanical performance of polymers. Graphical abstract: Image 10323 Highlights: The WPU and amine intercalated α-ZrP (WPU/fZrP) nanocomposites were prepared by in situ polymerization. The WPU/fZrP exhibit excellent tensile and thermal properties compared to the pristine WPU and WPU/ZrP nanocomposites. The amine intercalated α-ZrP had shown better exfoliation in WPU matrix compared to the unmodified α-ZrP. The thermal conductivity, water resistance and water stability of WPU/fZrP nanocomposites improved drastically.